Javanese and the Samin Community: A Reflection of Ideology and Identity of Its Speakers - Suhandano Suhandano (Humaniora, 2020)
Javanese has several variants, one of which is the Javanese spoken by the Samin community, a group of Javanese people who uphold Saminist teachings. This paper discusses the Javanese of the Samin people within the framework of anthropological linguistics, a study of languages in a cultural and social context. The paper addresses two questions: what are the characteristics of the Javanese spoken by the Samin people and why does their Javanese language have such these characteristics. Based on data gathered during extensive fieldwork, it was found that there are at least three characteristics of the Samin community’s Javanese: (i) Samin people tend to speak Javanese at the ngoko level; (ii) they use several specific words/lexicons; and (iii) different attitudes are shown in spoken communication. It seems that these three characteristics are related to their world view, ideology and identity. The Samin people, for example, consider that all people have the same status so there is no need to make these differentiations when speaking. That’s why they tend to speak Javanese at the ngoko level and address others by the same word sedulur, meaning relatives. Likewise, their attitude in speaking, such as leaving a conversation before it becomes a quarrel, reflects their view that a quarrel tends to hurt others so must be avoided. These findings reinforce the view that language is closely related to the speaker’s world view that is, their ideology and identity. The relationship of ideology, language and identity, in the case of the Samin people, seems to be a linear progression. Their ideology influences their language, and then, their language constructs their identity. The study of language in the socio-cultural context of the speakers not only provides a better understanding of the language but also a better understanding of the characteristics of the speakers.